The Influence of the Jigsaw Type Cooperative Learning Model on Students' Learning Motivation in Social Sciences Learning - Lindawati, Lindawati; Tetep; Lili Dianah (Institut Pendidikan Indonesia, 2024)
The background of this research is that educators carry out learning using conventional learning which also influences students' learning motivation. student learning outcomes on social studies subjects are still low. So that the quality of social studies learning cannot achieve optimal results, because there are still many students who have negative perceptions of social studies subjects. The purpose of this study was to identify an increase in student learning outcomes when using the jigsaw type learning method. The research method used is quantitative method with this type of research is Quasi Experimental Design (quasi-experimental). Data collection techniques were carried out by observation, interviews and documentation studies. Data analysis techniques used the normality test, homogeneity test, hypothesis testing and normalized gain test to identify improvements in the results of the research conducted. The results of data analysis and statistical calculations show that there is a significant increase in social studies learning outcomes using the jigsaw type cooperative learning model. The results of data analysis and statistical calculations and interviews show that the attitude of students towards the jigsaw type cooperative learning model in general shows a very good attitude and the attitude of students towards the jigsaw type cooperative learning model for each individual shows a very good attitude, so it can be concluded that the scale interpretation the attitude of students towards the jigsaw type cooperative learning model is in the very good category.